High-modulus high-thermal-conductivity aluminum-based composite material and preparation method thereof

By in situ generating nanoparticles and CNTs@Al3BC core-shell structures in aluminum-based composite materials, the problems of insufficient elastic modulus and thermal conductivity of traditional aluminum alloys are solved, and the preparation of high modulus and high thermal conductivity of aluminum-based composite materials is achieved.

CN119843111AActive Publication Date: 2025-04-18SHANDONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510079258.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-18
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

Traditional aluminum alloys have low elastic modulus and insufficient thermal conductivity, making it difficult to meet the demand for high modulus and high thermal conductivity of modern manufacturing, especially in the fields of automobiles, electronic communications and defense industries.

Method used

Through the liquid-solid reaction of Al and boron plastids, nanoparticles (γ-Al2O3 or/and AlN) distributed in a network along the grain boundary are generated in situ, and the Al and B elements react in a finite interface with CNTs to generate Al3BC, forming CNTs@Al3BC particles with core-shell structures, enhancing the stiffness and thermal conductivity of the material.

Benefits of technology

The elastic modulus of aluminum-based composite materials has been increased to 95~120GPa and the thermal conductivity has reached 150~180Wm-1K-1, avoiding the material brittleness caused by weak interface bonding strength between CNTs and Al matrix.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843111A_ABST
    Figure CN119843111A_ABST
Patent Text Reader

Abstract

The invention provides a high-modulus and high-thermal-conductivity aluminum-based composite material and a preparation method thereof. The aluminum-based composite material comprises an aluminum matrix and a reinforcing phase, wherein the reinforcing phase comprises CNTs (at) Al3BC particles of a core-shell structure and nano-reinforced particles generated in situ; the mass percentage of the CNTs added in the composite material is 0.5-3.0%, and the CNTs (at) Al3BC particles of the core-shell structure are uniformly distributed among aluminum matrix crystal grains; the nano reinforced particles generated in situ are gamma-Al2O3 (aluminum oxide) and / or AlN (aluminum nitride); the in-situ generated nano reinforced particles are distributed along the grain boundary of aluminum matrix grains, and the mass percent of the in-situ generated nano reinforced particles is 2.9-16.4%. The invention also provides a preparation method of the composite material. The composite material has high modulus and high thermal conductivity, the elastic modulus of the composite material reaches 95-120 GPa, and the thermal conductivity of the composite material reaches 150-180 Wm <-1 > K <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal-based composite materials, and in particular relates to a high-modulus and high-thermal-conductivity aluminum-based composite material and a preparation method thereof. Background Art

[0002] Aluminum alloys have excellent mechanical and thermophysical properties such as low density, corrosion resistance and high specific strength, and are important basic materials in the manufacturing industry. The density of aluminum is only 1 / 3 of that of steel, but its thermal conductivity is 3 times that of iron. However, the elastic modulus (stiffness) of traditional aluminum alloys is relatively low, only about 70GPa, which significantly affects its application in the fields of automobiles, electronic communications, and defense industries. In addition, with the increasing requirements for energy conservation, emission reduction, and lightweight development, structural parts such as heat dissipation housings tend to be miniaturized and lightweight, and the increase in power density leads to an increasing requirement for thermal conductivity of structural parts. However, the thermal conductivity of conventional aluminum alloys cannot meet the increasing requirements for heat dissipation performance. Therefore, the research and development of high modulus and high thermal conductivity aluminum-based composite materials has important application prospects and practical significance.

[0003] In order to improve the elastic modulus of aluminum alloys, current research at home and abroad can be summarized into two directions: alloying and the development of particle-reinforced aluminum-based composite materials. Among the alloying elements, Li is the most effective in improving the elastic modulus of aluminum alloys. However, the Al-Li alloy surface processing conditions are harsh, the weldability is poor, and the elastic modulus is generally still not higher than 92GPa. Since reinforcing particles (such as SiC, TiC, TiB2, etc.) have a high elastic modulus, introducing reinforcing particles into the aluminum matrix to develop aluminum-based composite materials is an effective strategy to improve the strength of aluminum alloys. Among them, carbon nanotubes (CNTs) have extremely high theoretical elastic modulus values ​​(about 1TPa) and excellent thermal conductivity (300-3000Wm -1 K -1 ), is a very promising reinforcement for aluminum-based composites. However, the interface bonding strength formed between CNTs and the aluminum matrix is ​​weak. When an external load is applied to the CNTs-Al composite, the CNTs / Al interface often debonds, making it impossible to effectively transfer the load, causing the material to break easily. To address this problem, a number of studies have proposed methods to in-situ convert the outer layer of CNTs into phases such as Al4C3 to improve interface bonding. However, Al4C3 particles are easily hydrolyzed and brittle, which significantly affects the mechanical properties of the composite.

[0004] Therefore, it is of great significance to develop a simple in-situ generation method for preparing carbon nanotube (CNTs) reinforced high modulus and high thermal conductivity aluminum-based composite materials. To this end, the present invention is proposed. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a high modulus and high thermal conductivity aluminum-based composite material and a preparation method thereof. The present invention uses the liquid-solid reaction of Al and boron (B2O3 or / and BN) to, on the one hand, in-situ generate nanoparticles (γ-Al2O3 or / and AlN) distributed in a network along the grain boundary, which effectively contributes to the stiffness and strength of the material. On the other hand, the Al and B elements react with CNTs to generate Al3BC by limited interface reaction, which fully utilizes the contribution of CNTs to the thermal conductivity of the material and avoids the disadvantage that the material is easily damaged due to its weak interface bonding strength with the Al matrix, thereby preparing a high modulus and high thermal conductivity aluminum-based composite material.

[0006] The present invention is achieved in the following ways: A high modulus and high thermal conductivity aluminum-based composite material, comprising an aluminum matrix and a reinforcement phase, wherein the reinforcement phase comprises CNTs@Al3BC particles with a core-shell structure and nano-reinforced particles generated in situ; the CNTs@Al3BC particles with a core-shell structure have externally added CNTs as cores and in-situ generated Al3BC particles as shells, and have a core-shell structure of Al3BC coating CNTs; the mass percentage of the externally added CNTs in the composite material is 0.5-3.0%, and the CNTs@Al3BC particles with a core-shell structure are uniformly distributed between aluminum matrix grains; the in-situ generated nano-reinforced particles are γ-Al2O3 and / or AlN; the in-situ generated nano-reinforced particles are distributed along the grain boundaries of the aluminum matrix grains, and the mass percentage of the in-situ generated nano-reinforced particles is 2.9-16.4%.

[0007] Preferably according to the present invention, the size of the aluminum matrix grains is 0.2-1.5 μm.

[0008] Preferably according to the present invention, the added CNTs are multi-walled CNTs with a diameter of 30-100 nm, more preferably 30-50 nm, and a length of 10-50 μm, more preferably 10-20 μm; the multi-walled carbon nanotubes are common commercial products.

[0009] Preferably according to the present invention, the size of the in-situ generated Al3BC particles is 0.1-1 μm.

[0010] Preferably according to the present invention, the size of the in-situ generated nano-enhanced particles is 5-100 nm.

[0011] The method for preparing the high modulus and high thermal conductivity composite material comprises the following steps: (1) Prepare the required raw materials according to the following mass percentages: aluminum powder 86.7~97.4%, boron 2.0~10.0%, CNTs powder 0.5~3.0%, catalyst 0.1~0.3%; (2) mixing the aluminum powder, boron body, CNTs powder and catalyst in step (1), and ball milling the obtained material under an argon atmosphere to obtain a mixed material; (3) degassing and encapsulating the mixed material obtained in step (2), and pressing it into a preform in a cold isostatic press; (4) The preform is placed in a heating furnace for heat preservation treatment, and then extruded by a hot extruder to obtain a high modulus and high thermal conductivity aluminum-based composite material.

[0012] Preferably according to the present invention, the size of the aluminum powder in step (1) is ≤80 μm, more preferably 1-50 μm.

[0013] Preferably according to the present invention, the boron body in step (1) is B2O3 and / or BN, and the size of the boron body is ≤10 μm, more preferably 1-5 μm.

[0014] Preferably according to the present invention, the diameter of the CNTs powder in step (1) is 30-100 nm, more preferably 30-50 nm, and the length is 10-50 μm, more preferably 10-20 μm; the CNTs powder is multi-walled carbon nanotube powder.

[0015] Preferably, according to the present invention, the catalyst in step (1) is graphene oxide, which can be commercially available or prepared according to existing methods.

[0016] Preferably, according to the present invention, the rotation speed of the ball mill in step (2) is ≥300 r / min, more preferably 300-400 r / min; the ball milling time is 1-5 h, and the ball-to-material ratio is 5-12:1.

[0017] Preferably according to the present invention, in step (3), the pressure of the cold isostatic press is 210-300 MPa.

[0018] Preferably, according to the present invention, the temperature of the heat preservation treatment in step (4) is 580-800° C., and the time of the heat preservation treatment is 0.5-4 h.

[0019] Preferably, according to the present invention, the extrusion ratio of the extruder in step (4) is 5-25:1.

[0020] The technical features and beneficial effects of the present invention are as follows: 1. The γ-Al2O3, AlN and Al3BC particles in the aluminum-based composite material of the present invention are self-generated in situ, with a clean and pollution-free surface and high interfacial bonding strength with the aluminum matrix. The γ-Al2O3 and / or AlN nanoparticles are distributed in a three-dimensional network along the grain boundaries of the matrix grains, which can give full play to the role of configuration strengthening and improve the strength and modulus of the material; the high-modulus and high-thermal-conductivity CNTs form CNTs@Al3BC core-shell structured composite particles in situ, which are dispersed between the grains, effectively enhancing the material stiffness and thermal conductivity, and achieving a strong bond with the aluminum matrix, preventing the formation of the brittle phase Al4C3. Based on the above-mentioned types of synergistic composite strengthening with different distributions, different sizes, and different structural phases, the elastic modulus of the composite material can reach 95~120GPa, and the thermal conductivity can reach 150~180Wm -1 K -1 .

[0021] 2. A specific amount of catalyst is added to the aluminum-based composite material of the present invention, which can not only reduce the reaction temperature and regulate the reaction process, but also prevent the Al3BC particles from growing into needle-like and other unfavorable morphologies. In addition, since the densities of γ-Al2O3, AlN, Al3BC and CNTs are not high, the density of the composite material prepared by this method is ≤3.0g / cm 3 , with remarkable lightweight characteristics.

[0022] 3. The method of the present invention is simple in process. The mass percentage and distribution characteristics of the enhanced particles can be adjusted by changing the ratio of aluminum powder, boron and CNT powder. The scale of γ-Al2O3 and / or AlN particles and the size of each part of the CNTs@Al3BC core-shell structure can be controlled by changing the insulation temperature and time, thereby customizing the elastic modulus and thermal conductivity of the composite material according to application requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the microstructure of the high modulus and high thermal conductivity aluminum-based composite material of the present invention; in the figure, 1 is the aluminum matrix grain, 2 is the nano-reinforced particles distributed along the grain boundary, 3 is the in-situ endogenous Al3BC coating layer, and 4 is the CNTs reinforcement phase.

[0024] Figure 2 This is a transmission electron microscope photograph of the microstructure of the high modulus and high thermal conductivity aluminum-based composite material prepared in Example 1; in the figure, 1 is nano γ-Al2O3 particles, 2 is CNTs, 3 is Al3BC, and 4 is aluminum matrix.

[0025] Figure 3 This is a high-resolution transmission electron microscopy photograph of CNTs@Al3BC core-shell structure particles in the high modulus and high thermal conductivity aluminum-based composite material prepared in Example 1; in the figure, 1 is the lattice fringes of Al3BC particles, and 2 is the lattice fringes of CNTs. DETAILED DESCRIPTION

[0026] The present invention will be further described below with reference to specific embodiments, but is not limited thereto.

[0027] Meanwhile, the experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents, materials and equipment described are all commercially available unless otherwise specified.

[0028] The purity of the aluminum powder, boron body and multi-walled CNTs powder used in the examples is 99.9%. Example 1

[0029] A method for preparing a high modulus and high thermal conductivity aluminum-based composite material comprises the following steps: (1) Prepare the required raw materials according to the following mass percentages: spherical aluminum powder 92.3% (size 1 μm), boron (B2O3 powder) 5.0% (size 1 μm), CNTs powder 2.5% (multi-walled, diameter 30 nm, length 10 μm), catalyst (graphene oxide) 0.2%; (2) The spherical aluminum powder, boron body, CNTs powder and catalyst in step (1) are mixed, and the obtained material is subjected to high-speed ball milling (ball mill speed of 360 r / min) for 2 h under an argon atmosphere, with the ball-to-material ratio set at 7:1, to obtain a mixed material; (3) degassing and encapsulating the mixed material obtained in step (2), and pressing it into a preform in a cold isostatic press at a pressure of 210 MPa; (4) The preform is placed in a heating furnace, kept at 700°C for 1 hour, and extruded using a hot extruder with an extrusion ratio of 16:1 to obtain a high modulus and high thermal conductivity aluminum-based composite material.

[0030] In this embodiment, a high modulus and high thermal conductivity aluminum-based composite material reinforced with γ-Al2O3 and CNTs@Al3BC core-shell particles is obtained. The γ-Al2O3 particles have a size of about 20 nm and a mass fraction of 7.3%, and are distributed along the grain boundaries of the aluminum matrix. Al3BC particles are in situ formed around the CNTs particles, and the Al3BC particles have a size of about 500 nm. The formed core-shell CNTs@Al3BC particles are dispersed between the aluminum matrix grains. The transmission electron microscope photo is shown in FIG. Figure 2 As shown, the high-resolution transmission electron microscopy images of the CNTs@Al3BC core-shell structure particles in the composite material are shown in Figure 3 As shown; the elastic modulus of the composite material is 98GPa and the thermal conductivity is 162Wm -1 K -1 . Example 2

[0031] A method for preparing a high modulus and high thermal conductivity aluminum-based composite material comprises the following steps: (1) Prepare the required raw materials according to the following mass percentages: spherical aluminum powder 94.7% (size 20 μm), boron (BN powder) 2.0% (size 5 μm), CNTs powder 3.0% (multi-walled, diameter 50 nm, length 20 μm), catalyst (graphene oxide) 0.3%; (2) The high-purity spherical aluminum powder, boronite, CNT powder and catalyst in step (1) are mixed, and the resulting material is subjected to high-speed ball milling (ball mill speed of 300 r / min) for 5 h under an argon atmosphere, with the ball-to-material ratio set at 5:1, to obtain a mixed material; (3) degassing and encapsulating the mixed material obtained in step (2), and pressing it into a preform in a cold isostatic press at a pressure of 300 MPa; (4) The preform is placed in a heating furnace, kept at 800°C for 0.5 h, and extruded using a hot extruder with an extrusion ratio of 5:1 to obtain a high modulus and high thermal conductivity aluminum-based composite material.

[0032] In this embodiment, a high modulus and high thermal conductivity aluminum-based composite material reinforced with AlN and CNT@Al3BC core-shell particles is obtained. The AlN particles have a size of 80 nm and a mass fraction of 3.3%, which are distributed along the grain boundaries of the aluminum matrix. Al3BC particles are formed in situ around the CNTs particles. The Al3BC particles have a size of 1 μm, and the formed core-shell CNTs@Al3BC particles are dispersed between the aluminum matrix grains. The elastic modulus of the composite material is 105 GPa, and the thermal conductivity is 171 Wm -1 K -1 . Example 3

[0033] A method for preparing a high modulus and high thermal conductivity aluminum-based composite material comprises the following steps: (1) Prepare the required raw materials according to the following mass percentages: 89.4% spherical aluminum powder (size 50 μm), 10.0% boron (B2O3 and BN powder mixed in equal weight) (size 2 μm), 0.5% CNTs powder (multi-walled, diameter 40 nm, length 15 μm), and 0.1% catalyst (graphene oxide); (2) The high-purity spherical aluminum powder, boronite, CNTs powder and catalyst in step (1) are mixed, and the resulting material is subjected to high-speed ball milling (ball mill speed of 400 r / min) for 1 h under an argon atmosphere, with the ball-to-material ratio set at 10:1, to obtain a mixed material; (3) degassing and encapsulating the mixed material obtained in step (2), and pressing it into a preform in a cold isostatic press at a pressure of 250 MPa; (4) The preform is placed in a heating furnace, kept at 600°C for 3 hours, and extruded using a hot extruder with an extrusion ratio of 20:1 to obtain a high modulus and high thermal conductivity aluminum-based composite material.

[0034] In this embodiment, a high modulus and high thermal conductivity aluminum-based composite material reinforced with γ-Al2O3, AlN and CNTs@Al3BC core-shell particles is obtained. The γ-Al2O3 particle size is about 10nm, the mass fraction is 7.3%, the AlN particle size is 30nm, the mass fraction is 8.2%, and the two particles are distributed along the grain boundaries of the aluminum matrix; Al3BC particles are in situ formed around the CNTs particles, the Al3BC particle size is 200nm, and the formed core-shell structure CNT@Al3BC particles are dispersed between the aluminum matrix grains; the elastic modulus of the composite material is 115GPa, and the thermal conductivity is 156Wm -1 K -1 .

Claims

1. A high modulus and high thermal conductivity aluminum-based composite material, characterized in that: The aluminum-based composite material comprises an aluminum matrix and a reinforcement phase, wherein the reinforcement phase comprises CNTs@Al3BC particles with a core-shell structure and nano-reinforced particles generated in situ; the CNTs@Al3BC particles with a core-shell structure have externally added CNTs as cores and in-situ generated Al3BC particles as shells, and have a core-shell structure of Al3BC coating CNTs; the mass percentage of the externally added CNTs in the composite material is 0.5-3.0%; the CNTs@Al3BC particles with a core-shell structure are uniformly distributed between aluminum matrix grains; the in-situ generated nano-reinforced particles are γ-Al2O3 and / or AlN; the in-situ generated nano-reinforced particles are distributed along the grain boundaries of the aluminum matrix grains, and the mass percentage of the in-situ generated nano-reinforced particles is 2.9-16.4%.

2. The high modulus and high thermal conductivity aluminum-based composite material according to claim 1, characterized in that: The size of the aluminum matrix grains is 0.2-1.5 μm; the added CNTs are multi-walled CNTs with a diameter of 30-100 nm, preferably 30-50 nm, and a length of 10-50 μm, preferably 10-20 μm.

3. The high modulus and high thermal conductivity aluminum-based composite material according to claim 1, characterized in that: The size of the in-situ generated Al3BC particles is 0.1-1 μm; the size of the in-situ generated nano-enhanced particles is 5-100 nm.

4. A method for preparing the high modulus and high thermal conductivity composite material according to any one of claims 1 to 3, comprising the following steps: (1) Prepare the required raw materials according to the following mass percentages: aluminum powder 86.7~97.4%, boron 2.0~10.0%, CNTs powder 0.5~3.0%, catalyst 0.1~0.3%; (2) mixing the aluminum powder, boron body, CNTs powder and catalyst in step (1), and ball milling the obtained material under an argon atmosphere to obtain a mixed material; (3) degassing and encapsulating the mixed material obtained in step (2), and pressing it into a preform in a cold isostatic press; (4) The preform is placed in a heating furnace for heat preservation treatment, and then extruded by a hot extruder to obtain a high modulus and high thermal conductivity aluminum-based composite material.

5. The method for preparing the high modulus and high thermal conductivity aluminum-based composite material according to claim 4, characterized in that: The aluminum powder in step (1) has a size of ≤80 μm, preferably 1-50 μm.

6. The method for preparing the high modulus and high thermal conductivity aluminum-based composite material according to claim 4, characterized in that: The boron body in step (1) is B2O3 and / or BN, and the size of the boron body is ≤10 μm, preferably 1-5 μm.

7. The method for preparing the high modulus and high thermal conductivity aluminum-based composite material according to claim 4, characterized in that: The diameter of the CNTs powder in step (1) is 30-100 nm, preferably 30-50 nm, and the length is 10-50 μm, preferably 10-20 μm; the CNTs powder is multi-walled carbon nanotube powder.

8. The method for preparing the high modulus and high thermal conductivity aluminum-based composite material according to claim 4, characterized in that: The rotation speed of the ball mill in step (2) is ≥300 r / min, preferably 300-400 r / min; the ball milling time is 1-5 h, and the ball-to-material ratio is 5-12:

1.

9. The method for preparing the high modulus and high thermal conductivity aluminum-based composite material according to claim 4, characterized in that: In step (3), the pressure of the cold isostatic press is 210-300 MPa.

10. The method for preparing the high modulus and high thermal conductivity aluminum-based composite material according to claim 4, characterized in that: The temperature of the heat preservation treatment in step (4) is 580-800° C., and the time of the heat preservation treatment is 0.5-4 hours; the extrusion ratio of the extruder is 5-25:1.

Citation Information

Patent Citations

  • Preparation method of micro-nano dual-scale TiC particle reinforced aluminum matrix composite material

    CN113416861A

  • High-rigidity and high-strength aluminum-based composite material and preparation method thereof

    CN117684069A